2018
DOI: 10.1038/s41598-018-26693-x
|View full text |Cite
|
Sign up to set email alerts
|

Niche-induced extramedullary hematopoiesis in the spleen is regulated by the transcription factor Tlx1

Abstract: Extramedullary hematopoiesis (EMH) in postnatal life is a pathological process in which the differentiation of hematopoietic stem/progenitor cells (HSPCs) occurs outside the bone marrow (BM) to respond to hematopoietic emergencies. The spleen is a major site for EMH; however, the cellular and molecular nature of the stromal cell components supporting HSPC maintenance, the niche for EMH in the spleen remain poorly understood compared to the growing understanding of the BM niche at the steady-state as well as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 63 publications
1
48
0
Order By: Relevance
“…The dynamic role of the spleen in provisioning emergency hematopoiesis appears to rely on the rapid expansion of perivascular reticular cells that support HSCs . One possibility yet to be investigated is that mesenchymal stem and progenitor cells reside in spleen and quickly differentiate to expand stromal cells that form the niche.…”
Section: The Spleen Contains Perivascular Niches For Hscmentioning
confidence: 88%
See 4 more Smart Citations
“…The dynamic role of the spleen in provisioning emergency hematopoiesis appears to rely on the rapid expansion of perivascular reticular cells that support HSCs . One possibility yet to be investigated is that mesenchymal stem and progenitor cells reside in spleen and quickly differentiate to expand stromal cells that form the niche.…”
Section: The Spleen Contains Perivascular Niches For Hscmentioning
confidence: 88%
“…It has long been known that Hox11 (or Tlx1) expressed by splenic stromal cells is an essential transcription factor for spleen organogenesis . Overexpression of Tlx1 is sufficient to induce EMH in the absence of any other physiological stressor . When Tlx1 conditional knockout mice were investigated it was concluded that Tlx1‐expressing stromal cells are required for recruitment of HSCs into the spleen following EMH, and that those cells are a component of HSC niches in the spleen .…”
Section: The Spleen Contains Perivascular Niches For Hscmentioning
confidence: 99%
See 3 more Smart Citations